Morphological Variation In Atyaephyra Desmarestii (Millet, 1831) Within And Among Populations Over Its Geographical Range - ANASTASIADOU, CH.; KOUKOURAS, A.; MAVIDIS, M.; CHARTOSIA, N.; MOSTAKIM, MD.; CHRISTODOULOU, M.; ASLANOGLOU, CH. (Mediterranean Marine Science, 2004)
In order to elucidate the distinction of Atyaephyra desmarestii subspecies (A. d. desmarestii, A. d. orientalis, A. d. stankoi and A. d. mesopotamica ) and investigate their geographical distribution in Greece, the main morphological features and somatometric ratios were studied in numerous specimens collected from a dense station network of Greek fresh waters. Specimens from Belgium, Portugal, Albania and Turkey were also examined. Atyaephyra desmarestii was found in western and northern Greece while it was absent in eastern Greece , the Aegean and the Ionian islands. The comparison of the obtained data with those of the literature revealed a clearly overlapping variability of the main key morphological features among the four subspecies. The results of this study indicate that the current A. desmarestii subspecies are not valid on the basis of the used key features. There is only one very variable species with many ecophenotypes.